SPORT CENTER UNIVERSITAS TANJUNGPURA - Mahaghani, Muhammad Akrabbi; Caesariadi, Tri Wibowo; Affrilyno, Affrilyno (JMARS: Jurnal Mosaik Arsitektur, 2021)
Sports are activity carried out with the aim of getting physical and spiritual health. People of Pontianak, especially academic’s civitas at Tanjungpura University, often do sports activities. There are various ways to develop sports activities, one of which is providing a container that can accommodate sports activities, such as the "Sport Center of Tanjungpura University" with the aim of being a place for matches and training. By applying with a modern architectural approach can generate buildings that emphasize function, relations with the surrounding environment, honesty in the use of materials and simplicity. The planning method used in this report is by collecting data through descriptive methods. This method describes systematically, explains factually and accurately about the facts, nature and relationship of design requirements and design provisions to planning and design. Based on the terms and conditions of the design, which will be searched for the required data. The data collected will be analyzed in order to get clear conclusions and limitations regarding the planning and design of the Tanjungpura University Sport Center area in stages from general problems to detailed problems. The method of discussion will be carried out with the idea step, the problem identification step, the data collection step, the data analysis step, the synthesis step, and the design step. The result of the design of the author's final project is a sports building which consists of 2 floors with the building mass divided into 2 parts, namely the training building and the competition building. The building is designed using a minipile as the foundation, reinforced concrete frame as the column and beam structure, and steel as the roof frame material.